Life in the universe - Jeffrey Bennett; Shostak, Seth; Schneider; Macgregor, Meredith (New Jersey Princeton University Press, 2022)
Are we alone in the cosmos? How are scientists seeking signs of life beyond our home planet? Could we colonize other planets, moons, or even other star systems? This introductory textbook, written by a team of four renowned science communicators, educators, and researchers, tells the amazing story of how modern science is seeking the answers to these and other fascinating questions. They are the questions that are at the heart of the highly interdisciplinary field of astrobiology, the study of life in the universe. Written in an accessible, conversational style for anyone intrigued by the possibilities of life in the solar system and beyond, Life in the Universe is an ideal place to start learning about the latest discoveries and unsolved mysteries in the field. From the most recent missions to Saturn$1 (Bs moons and our neighboring planet Mars to revolutionary discoveries of thousands of exoplanets, from the puzzle of life$1 (Bs beginning on Earth to the latest efforts in the search for intelligent life elsewhere, this book captures the imagination and enriches the reader$1 (Bs understanding of how astronomers, planetary scientists, biologists, and other scientists make progress at the cutting edge of this dynamic field. Enriched with a wealth of engaging features, this textbook brings any citizen of the cosmos up to speed with the scientific quest to discover whether we are alone or part of a universe full of lifes
Keywords: Biology